Analysis of Attractiveness Store Atmosphere and Service Quality Towards Customer Loyalty Through Customer Satisfaction on The Renaissansi Coffe - Latifuddin, Muhammad Irfan; Lukitaningsih, Ambar; Cahyani, Putri Dwi (JEM17: Jurnal Ekonomi Manajemen, 2024)
This research aims to dissect and determine the influence of Attractiveness store Atmosphere & Service Quality on Customer loyalty through Customer satisfaction with Renaissance Coffee. This exploration uses a quantitative system and the population is coffee shop guests, especially those at Coffee Renaissance with a deliberate slice style. The results of this exploration show that the attractiveness of the store atmosphere has a direct negative and insignificant effect on Customer loyalty, service quality has a positive and significant effect on Customer loyalty, the attractiveness of the store atmosphere has a positive and significant effect on Customer satisfaction, service quality has a positive and significant effect on satisfaction. clients, has a positive and significant effect on Customer satisfaction and Customer satisfaction has a positive and significant effect on Customer loyalty. Keywords : Attractiveness Store Atmosphere, Service Quality, Customer Satisfaction, Customer Loyalty